Enhanced mechanical properties of 3D printed graphene-polymer composite lattices at very low graphene concentrations. (February 2020) - Markandan, Kalaimani; Lai, Chang Quan
Abstract: The advent of 3D printing has enabled the rapid prototyping of complex structures with relatively shorter production times and lower material wastage. Despite these advantages, it is still a challenge to fabricate nanofiller-reinforced lattices using 3D printing. Here, we report for the first time, the successful 3D printing of graphene-polymer octet-truss lattices using the stereolithography (SLA) technique. The factors influencing the mechanical properties of the printed graphene-polymer composite, such as filler concentration, solvent addition and post-fabrication baking temperature and duration were investigated in detail. Our results showed that stereolithographic 3D printing can confer the same improvement in material modulus with 10 times less graphene concentration compared to other processing techniques reported in literature. Our calculations suggest that this was due to a unique characteristic of stereolithography, which enabled the selection and incorporation of aligned graphene platelets into the polymer matrix during the 3D printing process. These exceptional mechanical properties of SLA fabricated polymer-graphene composites are indicative of their potential for use in various applications such as aerospace, automotive and sports equipment.